Hydrogeological reconnaissance of the river Tortuguero catchment in the Atlantic Zone of Costa Rica - Jong, T. de (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
Ilus. Tab. 10 ref. Sum. (En). También como: Field Report - Atlantic Zone Programme (CATIE) no. 124